geochemical characterization of dust from the Talos Dome ice core - Di Stefano, Elena (Università degli Studi di Siena, 2021)
Polar ice cores contain many proxies, of which mineral dust is a key one in understanding past climate variability. In fact, dust and climate have a strong influence on each other. Dust has both direct and indirect effects on climate by interacting with solar radiation and influencing cloud formation processes, while climate itself can strongly affect production, transport and deposition of dust. For example, it is well known that dust fluxes respond to the transition from glacial to interglacial regimes. Deposition of dust on the Antarctic continent is controlled by a number of climatic and environmental factors, and a reliable reconstruction of the dust record is essential to understand how these factors have changed in the past. But evidence has shown that, at certain depths in the ice, the dust record may be subjected to some degree of alteration. This work was conceived with the main objective of enhancing our comprehension of deep ice processes through the use of an array of different techniques applied to the Talos Dome ice core. In particular, we aim at studying the chemical and physical anomalies present in the deeper part of the dust record and confirm the existence of post-depositional processes which may alter the climatic signal embedded in deep ice. Moreover, we wish to observe how different elements partition between soluble and insoluble phase, at different depths of the ice core and link the geochemical patterns of the considered elements to the main climatic oscillations covered in the Talos Dome ice core. The Talos Dome ice core, drilled from a peripheral dome in Eastern Antarctica, is 1620m long and covers more than 250k years of climate history. We prepared samples from the entire length of the ice core, with a focus on depths lower than 1450m, which have not yet been dated. In this work, the published dust record has been integrated in its deepest part, by analyzing 125 samples through Coulter Counter. The dust concentration in the Talos Dome ice core exhibits the well known correlation ...